Electric field tuning non-volatile dynamic magnetism in half-metallic alloys Co2FeAl/Pb(Mg1/3Nb2/3)O3-PbTiO3 heterostructure. (29th March 2019) - Dunzhu, Gesang; Liu, Fufu; Wang, Yangping; Zhou, Cai; Jiang, Changjun
Abstract: The half-metallic characteristic of Co2 FeAl Huesler alloy films in Co2 FeAl/Pb(Mg1/3 Nb2/3 )O3 -PbTiO3 heterostructure was controlled by different substrate temperatures during deposition. The evolution of microstructure shows the B 2 ordering degree of Co2 FeAl thin film increase with the substrate temperature decreasing from 550 °C to 480 °C during deposition, which can be verified by anisotropy magnetoresistance measurement. Moreover, the result measured by rotating-angle ferromagnetic resonance demonstrates B 2 ordering degree of Co2 FeAl thin film controlled the change of symmetry of magnetic anisotropy. In addition, the loop -like curve of magnetic resonance field/linewidth versus electric field exhibits the non-volatile behavior, which can be attributed to the 109° ferroelectric domain switching of PMN-PT substrate. This result can provide opportunities for magnetization control in multiferroic devices.